Ternary Phase-Separation Investigation of Sol-Gel Derived Silica from Ethyl Silicate 40 - Wang, Shengnan (Sci Rep, 2015)
A ternary phase-separation investigation of the ethyl silicate 40 (ES40) sol-gel process was conducted using ethanol and water as the solvent and hydrolysing agent, respectively. This oligomeric silica precursor underwent various degrees of phase separation behaviour in solution during the sol-gel reactions as a function of temperature and H(2)O/Si ratios. The solution composition within the immiscible region of the ES40 phase-separated system shows that the hydrolysis and condensation reactions decreased with decreasing reaction temperature. A mesoporous structure was obtained at low temperature due to weak drying forces from slow solvent evaporation on one hand and formation of unreacted ES40 cages in the other, which reduced network shrinkage and produced larger pores. This was attributed to the concentration of the reactive sites around the phase-separated interface, which enhanced the condensation and crosslinking. Contrary to dense silica structures obtained from sol-gel reactions in the miscible region, higher microporosity was produced via a phase-separated sol-gel system by using high H(2)O/Si ratios. This tailoring process facilitated further condensation reactions and crosslinking of silica chains, which coupled with stiffening of the network, made it more resistant to compression and densification.